1987
DOI: 10.1136/jcp.40.7.725
|View full text |Cite
|
Sign up to set email alerts
|

Expression of class II major histocompatibility complex antigens on alveolar epithelium in interstitial lung disease: relevance to pathogenesis of idiopathic pulmonary fibrosis.

Abstract: To determine whether expression of class II major histocompatibility complex antigens on alveolar epithelium is relevant to the pathogenesis of idiopathic pulmonary fibrosis (IPF) lung biopsy specimens were investigated from nine patients with IPF with or without connective tissue disease, four patients with sarcoidosis, eight patients with lung disease of presumably infectious origin, and five controls. The alveolar epithelium stained strongly with anti-Ia (HLA-DR) or Leu 10 (HLA-DS) monoclonal antibodies, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Importantly, the expression of MHC class II molecules is actively regulated upon various cellular stimuli, and it has been demonstrated that alveolar epithelial cells from IPF lungs express HLA class II molecules (Kallenberg et al 1987). Moreover, some experimental work has shown that class II MHC antigens is expressed early on the type II alveolar epithelium and before any inflammatory cellular infiltration (Nakayama et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the expression of MHC class II molecules is actively regulated upon various cellular stimuli, and it has been demonstrated that alveolar epithelial cells from IPF lungs express HLA class II molecules (Kallenberg et al 1987). Moreover, some experimental work has shown that class II MHC antigens is expressed early on the type II alveolar epithelium and before any inflammatory cellular infiltration (Nakayama et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Although human and rat type II AEC express class II major histocompatibility complex (MHC) antigens on their cell surface, their role as antigen presenting cells has never been directly addressed (11,12,19,21). We hypothesize that type II AEC may function as antigen-presenting cells (APC) during pulmonary infection.…”
mentioning
confidence: 99%
“…However, accumulating evidence demonstrates that pulmonary alveolar epithelial cells not only function as a passive barrier mediating gas exchange but also actively participate in the host immune response. Alveolar epithelial cells are capable of processing and presenting antigen to T lymphocytes (18,19). Furthermore, isolated alveolar epithelial cells produce and secrete various cytokines and chemokines, including TNF␣ and MIP-2, when stimulated with bacterial components like li-popolysaccharide (LPS) or whole organisms such as Mycobacterium tuberculosis (20 -23).…”
mentioning
confidence: 99%